(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Discirculatory encephalopathy (DE) is a leading cause of neurodegeneration in individuals over 60 years of age. Meteorological sensitivity, exacerbating DE in 70% of patients, manifests as cephalgia, cognitive impairment, and autonomic crises, reducing quality of life. The absence of pathogenetic approaches to treatment defines the relevance of this study. Objective: To develop and evaluate the efficacy of a comprehensive treatment program for meteorological sensitivity in DE based on correction of autonomic dysregulation, serotonin deficiency, and impaired cerebral hemodynamics. Materials and Methods: 120 patients with DE stage 1–2 (64.2±7.8 years) with varying degrees of meteorological sensitivity were examined. Diagnostics included the SHOM scale, heart rate variability (HRV), platelet serotonin levels, and MMSE. The 12-week treatment program included non-pharmacological therapy, pharmacotherapy (vinpocetine, cinnarizine, sertraline, mexidol, citicoline), and transcranial micropolarization. Results: Statistically significant (p<0.001) improvement was achieved: headache frequency decreased by 52–62%, dizziness by 52–56%, SHOM scores by 42–48%. HRV parameters normalized (SDNN increase up to 67.0%), serotonin levels rose by up to 106.8%, and cognitive functions improved by up to 15.9%. Conclusion: Complex pathogenetic therapy is highly effective for meteorological sensitivity in DE patients, especially in severe forms.